NEW METHODOLOGY FOR CAPACITY CALCULATIONS IN THE LINE SECTION (BETWEEN TWO STATIONS) WITH AN INTERMEDIATE JUNCTION (Perner's Contacts, 2008)
Existing methods for capacity calculations in the line section (between two stations) with an intermediate junction are not satisfactory. To solve this problem, the article presents a scheme of a new methodology for these cases, which is (as much as possible) compatible with an existing method for capacity calculations according to the Capacity Leaflet (UIC 406).
Keywords: Capacity; Junction; Track of a line section